Book writers and article contributors celebrated - Safriza, Baharuddin (2020)
PEKAN, 13 November 2020 - Universiti Malaysia Pahang (UMP) Press published four new books entitled Harimau Yang Mengaum, Individual Field Project Guideline – Bachelor of Business Engineering with Honours, Module Strength of Materials 1, and Sensor and Instrumentation Systems.